Análise técnica e econômica do cultivo do Cajueiro-Anão (Anacardium occidentale L.) na regional de Jales-SP - de Araújo, Daniela Cintra [UNESP]; Tarsitano, Maria Aparecida Anselmo [UNESP]; da Costa, Thiago Vieira [UNESP]; Rapassi, Rosalina Maria Alves [UNESP] (My University, 2010)
It was aimed to estimate the production costs and profitability of the cashew in natura in the Region of Jales, northwest of the State of São Paulo. The data were collected with producers through a questionnaire application and elaboration of spreadsheets, to characterize the whole productive process and to accomplish economical analysis. The fruit production for table demands a system of more intensive cultivation mainly in the control of pests and diseases, as a result, the cost of the production is increased, is later, compensated by the best reached prices. The costs of the production are high, but what should be outstanding is the relative participation of the packing that can reach a third of the effective operational cost. The profitability indicators show that the cashew production is profitable in this area; the lucrativeness index was 46,50%.
Technical and economical analysis of Dwarf Cashew tree (Anacardium occidentale L.) Cultivation in the region of Jales-SP
Keywords: Cashew; Costs; Production system; Profitability